2017
DOI: 10.1016/j.jpor.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of accuracy and reproducibility of abutment position by intraoral scanners

Abstract: The results of this study indicated that an optical impression method with an intraoral scanner could be applied to the implant therapy for multiple teeth missing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
109
1
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 27 publications
7
109
1
7
Order By: Relevance
“…All datasets were converted to STL (Standard Triangulated Language [8], Standard Tessellation Language [19], and Stereolithography [21]) file format via manufacturers' certified software for standardization. Four datasets of 4 study models were taken from the reference scanner as reference data.…”
Section: Datasetsmentioning
confidence: 99%
See 2 more Smart Citations
“…All datasets were converted to STL (Standard Triangulated Language [8], Standard Tessellation Language [19], and Stereolithography [21]) file format via manufacturers' certified software for standardization. Four datasets of 4 study models were taken from the reference scanner as reference data.…”
Section: Datasetsmentioning
confidence: 99%
“…e clinical usage of intraoral scanners has become more and more common. For the last decade, the effectiveness of intraoral scanners was studied to prove their practicability in various clinical settings [1][2][3][4][5][6][7][8][9]. Digital impression systems, when proving their credibility to replace conventional impression methods will benefit the orthodontic clinicians and patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accuracy consists of trueness and precision (ISO 5725‐1) (ISO, ), and high accuracy is essential for fabricating precise prosthetic appliances (Fukazawa et al, ). Trueness indicates how much a measurement deviates from the actual object, while precision describes how close repeated measurements are to each other (Flügge et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the RMS value is the standard for the evaluation of the accuracy of the scanning data in many studies [13][14][15]17]. The previous studies found that deviation of more than 100 µm from the complete arch resulted in an inaccurate fit of the final restoration in the maxilla and mandible [3,9] Also, an allowable range of less than 100 µm was proposed as an acceptable cement space for the prosthesis [3,18].…”
Section: Introductionmentioning
confidence: 99%